Celebrating the gift of Jesus - Fearon, Mary, Sister; Hirstein, Sandra J. (Dubuque, Iowa : BROWN-ROA, 1993)
Catechetical program that prepares young children to celebrate Jesus in the gift of the eucharist.
Keywords: Jesus Christ -- Juvenile literature; Lord's Supper -- Catholic Church -- Juvenile literature